Casca de banana e baraço de batata-doce em dietas para coelhos de corte - Falcone, Diuly Bortoluzzi (2023)
The present work was developed to evaluate the use of banana peel (BP) and sweet potato vines (SPV) in the diet of growing rabbits. For this, a biological assay was developed with different levels of BP and SPV in substitution of maize and alfalfa hay. The same was treated for 49 days, in a completely randomized design, in the Laboratory of Cuniculture of the Department of Animal Science of the Federal University of Santa Maria. New Zealand White rabbits were used, with an initial age of 35 days (±614g) and a final age of 84 days. The biological test consisted of five isonutritive diets, with 10 animals in each treatment, the increasing replacement of maize by banana peel and alfalfa hay by sweet potato vines was used to compose the treatments: he control diet (0) without BP and SPV; (25) experimental diet with 25% BP and SPV as maize and alfalfa hay substitute; (50) experimental diet with 50% BP and SPV as maize and alfalfa hay substitute; (75) experimental diet with 75% BP and SPV as maize and alfalfa hay substitute; and (100) experimental diet with 100% BP and SPV as maize and alfalfa hay substitute. The variables evaluated were performance (feed intake, mass gain and feed conversion), carcass and meat characteristics, carcass yield and coat characteristics. Data were compared using analysis of variance of means, followed by the Tukey test at 5% significance. Subsequently, an economic study was carried out based on the effective operating costs and profitability of each of the workers. It was possible to verify that the BP and the SPV did not influence the performance variables, as well as the centesimal and color characteristics (L*, a* and b*) of the meat, which remained the same, regardless of the levels used of BP and SPV in the diet. As for the economic results, the linear reduction in the cost of the feed stands out, with the experimental diet T100 (with 100% replacement of maize and alfalfa hay by BP and SPV) less costly and more profitable when compared to the control treatment. The replacement of maize and alfalfa hay by BP and SPV in rabbits' diets, in addition to reducing production costs, can also be used as a mitigating tool to combat food insecurity. Based on the parameters studied, it is concluded that BP and SPV can completely replace maize and alfalfa hay in diets for growing rabbits, without causing changes in the zootechnical performance of the animals.